Influence of Mortar Incorporating Silica Based Waste Material on the Formation of C-S-H and Mechanical Strength Properties - Nafisa, Tamanna; Norsuzailina, Mohamed Sutan; Ibrahim, Yakub; Teo, Delsye Ching Lee; Ezzaq Farhan, Ahmad (Trans Tech Publications, Switzerland, 2015)
Recent studies have been carried out to utilize waste glass in construction as partial cement replacement. This paper investigates the formation of Calcium Silicate Hydrate (C-S-H) and strength characteristics of mortar in which cement is partially replaced with glass powder by replacement level of 10%, 20% and 30%. Mortar cubes containing varying particle sizes in the ranges of 150-75μm, 63-38 μm and lower than 38 μm and in a water to cement ratio of 0.45 and 0.40 have been prepared. Replacement by 10% cement with glass powder reveals high compressive strength and produces more C-S-H at 28 days than other levels of replacement.